A Comprehensive Study of Repetitive Transcranial Magnetic Stimulation in Parkinson's Disease. (8th August 2011) - Kimura, Hideki; Kurimura, Masayuki; Kurokawa, Katsurou; Nagaoka, Utako; Arawaka, Shigeki; Wada, Manabu; Kawanami, Toru; Kurita, Keiji; Kato, Takeo
Abstract : The clinical benefits of repetitive transcranial magnetic stimulation (rTMS) for Parkinson's disease (PD) remain controversial. We performed a comprehensive study to examine whether rTMS is a safe and effective treatment for PD. Twelve PD patients received rTMS once a week. The crossover study design consisted of 4-week sham rTMS followed by 4-week real rTMS. The Unified Parkinson's Disease Rating Scale (UPDRS), Modified Hoehn and Yahr Stage, Schwab and England ADL Scale, Actigraph, Mini-Mental State Examination, Hamilton Depression Scale, Wechsler Adult Intelligence Scale-revised, and cerebral blood flow (CBF) and cerebrospinal fluid (CSF) examinations were used to evaluate the rTMS effects. Under both drug-on and drug-off conditions, the real rTMS improved the UPDRS scores significantly, while the sham rTMS did not. There were no significant changes in the results of the neuropsychological tests, CBF and CSF. rTMS seems to be a safe and effective therapeutic option for PD patients, especially in a wearing-off state.